SIMULATION ANALYSIS OF THE VOID LOCATION DURING THE ELECTROMIGRATION BASED ON ATOMIC CONCENTRATION - YANG Jing; JIANG YiMing; CHEN Gang; XU WeiLing (Jixie qiangdu)
With the development of electronic packaging towards high power and high density,the interconnection structure is faced with the reliability problem induced by electromigration. Most traditional simulation methods are based on a single or two physical fields. Herein,a simulation method for obtaining the distribution of atomic concentration in interconnection structures under the effect of complete coupling of electric field,temperature field,stress field and atomic concentration field was proposed to predict the void at the minimum value of atomic concentration using finite element method. This method is applied to interconnect lead structure and interconnect welding ball structure,respectively. And the accuracy and reliability of this method are verified by comparing experimental phenomena,which provides a precise prediction method for the reliability analysis of integrated circuit design.